Bcl-2 and p53 overexpression as associated risk factors in transitional cell carcinoma of the bladder - (:unkn) unknown (Akademiai Kiado Rt., 1998)
Bcl-2 and p53 genes are implicated in cell cycle regulation with roles on programmed cell death. Consequently, presence of Bcl-2 and nuclear accumulation of p53 were proposed to confer a growth advantage tumour cells. We have investigated their role as prognostic factors in fresh tumour samples from a cohort of twenty patients with transitional cell carcinoma of the bladder by immunohistochemical analysis in paired specimens. Expression of Bcl-2 was observed in 11 cases (69%) and nuclear p53 accumulation in 9 (45%). In the presence of Bcl-2 protein expression, tumours showed a slightly higher rate of recurrence (55% vs. 40%) and significantly more progression (36% vs. 0%). Recurrence and progression rates were not significantly different in tumours with and without nuclear p53 overexpression (recurrence rates 56% vs. 55% and progression rates 33% vs. 27%, respectively). Grade and stage appeared as important prognosticators since 75% of grade 3 tumours showed recurrence and 50% progressed in contrast to 44% and 13%, respectively, of grades 1 and 2 tumours. Similarly, 50% of Ta-T1 tumours recurred and 20% progressed, while these rates were 75% and 75% for T2-T3 tumours. Also, expression of Bcl-2 and nuclear accumulation of p53 correlated with grade. In grade 3 tumours, 75% showed nuclear p53 overexpression and 80% cytoplasmic Bcl-2 protein. These figures were 25% and 64% for grades 1 and 2 tmours. In conclusion, Bcl-2 protein expression in transitional cell carcinoma appears to be associated with a poorer prognosis and together with nuclear p53 overexpression they are associated with tumour de-differentiation.